Metakaolin-dye-water reducing agent synergistically dispersed colored UHPC (Ultra High Performance Concrete) and preparation method thereof

Through the synergistic dispersion technology of metakaolin-dye-water reducing agent, the problems of uneven dispersion of dyes and reduced fluidity in colored concrete are solved, and the uniform dispersion and durability of dyes are achieved, which enhances the strength and application value of UHPC.

CN119263746AInactive Publication Date: 2025-01-07河南省第二建设集团有限公司 +1

Patent Information

Application Number
CN202411804690.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-01-07
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In the existing color concrete preparation technology, there are problems such as uneven dispersion of dyes, agglomeration of dyes, easy fading, hand staining and reduced fluidity, which affects its aesthetics and service life.

Method used

The synergistic dispersion method of metakaolin-dye-water reducing agent is adopted. Through magnetic stirring and ultrasonic dispersion technology, the dye is evenly dispersed in metakaolin, combining cement, quartz sand and steel fibers to form an optimized concrete-based material.

Benefits of technology

It achieves uniform dispersion and high durability of dyes, is not easy to fade and stick to hands, enhances the strength and integrity of concrete, and improves the application value of UHPC.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119263746A_ABST
    Figure CN119263746A_ABST
Patent Text Reader

Abstract

The invention relates to the field of building materials, and particularly discloses color UHPC with metakaolin-dye-water reducer synergistically dispersed and a preparation method thereof. 20%-50% by mass of metakaolin, the total mass of dye, 50%-100% by mass of water and 100% by mass of water reducing agent are put into a magnetic stirrer to be stirred for about 10 minutes, preliminary stirring is formed, and a mixed solution is formed; after stirring by a magnetic stirrer, taking out all mixed liquid, putting the mixed liquid into an ultrasonic dispersion instrument, and stirring at the power of 800W for 10-20 minutes. Through the method, the homogeneity of the dye in the color UHPC can be effectively improved, the dye agglomeration phenomenon is reduced, the coloring rate is high, and the fluidity of the UHPC under the same condition can be improved. The UHPC processed by the method does not fade, does not stick to hands, and has no bubbles and defects on the surface.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of building materials, and in particular to a color UHPC with synergistic dispersion of metakaolin, dye and water reducing agent and a preparation method thereof. Background Art

[0002] The existing color concrete preparation technology has technical problems such as uneven dye dispersion, dye agglomeration, easy fading, and staining, which seriously affect the appearance and service life of colored concrete. When dyes are added to ordinary concrete, they consume the free water in the concrete, reduce its fluidity, make it difficult to pour, and easily produce surface defects and holes, which in turn affects its aesthetics.

[0003] UHPC has a longer service life than ordinary concrete, so fully dispersing the colorant, preventing it from agglomerating and distributing it evenly, has greater value than using it in ordinary concrete. Summary of the invention

[0004] In view of the shortcomings of the prior art, the present invention uses a new collaborative dispersion method, the purpose of which is to optimize the color UHPC technology and solve technical problems such as uneven dye dispersion, dye agglomeration, easy fading, staining, and reduced fluidity.

[0005] The invention provides a color UHPC with synergistic dispersion of metakaolin, dye and water reducing agent. The color UHPC comprises cement, metakaolin, white silica fume, quartz sand, water, steel fiber, water reducing agent and dye.

[0006] Furthermore, in parts by mass, cement is 950-1100 parts, metakaolin is 150-200 parts, white silica fume is 0-150 parts, quartz sand is 1000-1400 parts, steel fiber is 100-400 parts, water reducer is 40-80 parts, water is 189-270 parts, and dye is 30-70 parts.

[0007] Furthermore, the cement is PO 52.5 white cement with a whiteness of ≥85; the specific surface area of ​​the metakaolin is ≥15m 2 / g, whiteness ≥90; the specific surface area of ​​the white silica fume ≥12 m 2 / g, whiteness ≥90.

[0008] Furthermore, the quartz sand particles range from 0.106 to 0.212 mm; the water reducer is a polycarboxylic acid water reducer; and the steel fiber has a length of ≥12 mm and a diameter of ≤0.2 mm.

[0009] Furthermore, the dye is an iron oxide-based dye for concrete.

[0010] The present invention provides a method for preparing the above-mentioned metakaolin-dye-water reducing agent synergistically dispersed colored UHPC, comprising the following steps: S1: Depending on the size of the prepared component, all the weight of the dye, 20% to 50% weight of kaolin, 50% to 100% weight of water, and 100% weight of the water reducer are placed in a magnetic stirrer and stirred for about 10 minutes to form a preliminary stirring to form a mixed liquid; wherein the weight ratio of dye: kaolin: water: water reducer is (2-3): (3-5): (5-10): (2-3); through the synergistic dispersion of kaolin-dye-water reducer, the dye can be evenly dispersed in the kaolin particles smaller than cement particles in the system, so that the dye is evenly dispersed, the dye does not agglomerate, the dye has high durability, does not fade, and does not stick to the hands; S2: The mixed solution obtained in step S1 is placed in a magnetic stirrer and stirred for 10 minutes. After being stirred in the magnetic stirrer, all the mixed solution is taken out and placed in an ultrasonic disperser, and stirred at a power of 800 W for 10-20 minutes; S3: adding the mixed solution treated in step S2 into a concrete mixer, and adding the remaining cement, water, metakaolin, white silica fume, and quartz sand into the concrete mixer and stirring for 2-3 minutes until a plastic cement-based slurry is formed; S4: gradually add steel fibers into the concrete mixer, adding about 10% of the total amount of steel fibers each time, and continue to add steel fibers until all steel fibers are added after no steel fibers are visible on the visible surface of the mixer; S5: After the last batch of steel fibers is added, continue stirring for about 1 minute, take out the concrete, and pour it into the mold; S6: After one day of curing at room temperature, demould and check the apparent color difference and the presence of pores.

[0011] The prepared kaolin-dye-water reducer synergistically dispersed colored UHPC can be used in a range of applications including but not limited to exterior wall panels, imitation rock panels, and imitation ceramic panels, and can be pre-embedded with connectors inside, and can be well used in the construction industry, decoration industry, and daily necessities industry. Beneficial Effects

[0012] 1. Through the synergistic dispersion of metakaolin-dye-water reducing agent, the dye can be evenly dispersed in the metakaolin in the system, which is smaller than cement particles, so that the dye is evenly dispersed, the dye does not agglomerate, has high durability, does not fade, and does not stick to hands.

[0013] 2. The synergistic dispersion further enhances the performance advantages of kaolin in the system, so that kaolin can optimize the particle distribution in cement-based materials in the concrete system, produce the densest packing effect, and increase strength.

[0014] 3. Synergistic dispersion increases the Al element concentration in cement-based materials, enhances the CSH gel strength, and improves the strength of UHPC.

[0015] 4. Synergistic dispersion enables dye particles, kaolin, cement, white silica fume and quartz sand to form a continuous particle gradation, reducing the harmful pore content and enhancing the integrity of the structure.

[0016] 5. Synergistic dispersion homogenizes the content of kaolin-dye-water reducer in each part of UHPC, so that the above-mentioned components are transformed from discrete distribution to linear distribution in the system, improving homogeneity. Compared with cement as the dispersion medium, the kaolin-dye-water reducer dispersion medium has a wider particle distribution and contains both solid and liquid phases, so it has a better effect.

[0017] 6. In ultra-thin plates, synergistic dispersion can make both the front and back surfaces present good and uniform effects, which is conducive to its use in special thin-walled structures. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 This is a UHPC specimen that has been processed by collaborative dispersion.

[0019] Figure 2 This is a UHPC specimen without co-dispersion treatment.

[0020] Figure 3 This is the preparation process of the colored UHPC of the present invention. DETAILED DESCRIPTION

[0021] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0022] The present invention provides an embodiment: a color UHPC with synergistic dispersion of metakaolin, dye and water reducing agent, wherein the raw materials include cement, metakaolin, white silica fume, quartz sand, steel fiber, water reducing agent, water and dye.

[0023] Furthermore, the cement is PO 52.5 white cement with a whiteness of ≥85; the specific surface area of ​​the metakaolin is ≥15m 2 / g, whiteness ≥90; the specific surface area of ​​the white silica fume ≥12 m 2 / g, whiteness ≥90.

[0024] Furthermore, the quartz sand particles range from 0.106 to 0.212 mm; the water reducer is a polycarboxylic acid water reducer; and the steel fiber has a length of ≥12 mm and a diameter of ≤0.2 mm.

[0025] Furthermore, the dye is an iron oxide-based dye for concrete.

[0026] The present invention provides another embodiment: a method for preparing a colored UHPC with synergistic dispersion of metakaolin, dye and water reducing agent, comprising the following steps: S1: Depending on the size of the prepared component, all the weight of the dye, 20% to 50% weight of kaolin, 50% to 100% weight of water, and 100% weight of the water reducer are placed in a magnetic stirrer and stirred for about 10 minutes to form a preliminary stirring to form a mixed liquid; wherein the weight ratio of dye: kaolin: water: water reducer is (2-3): (3-5): (5-10): (2-3); through the synergistic dispersion of kaolin-dye-water reducer, the dye can be evenly dispersed in the kaolin particles smaller than cement particles in the system, so that the dye is evenly dispersed, the dye does not agglomerate, the dye has high durability, does not fade, and does not stick to the hands; S2: The mixed solution obtained in step S1 is placed in a magnetic stirrer and stirred for 10 minutes. After being stirred in the magnetic stirrer, all the mixed solution is taken out and placed in an ultrasonic disperser, and stirred at a power of 800 W for 10-20 minutes; S3: adding the mixed solution treated in step S2 into a concrete mixer, and adding the remaining cement, water, metakaolin, white silica fume, and quartz sand into the concrete mixer and stirring for 2-3 minutes until a plastic cement-based slurry is formed; S4: gradually add steel fibers into the concrete mixer, adding about 10% of the total amount of steel fibers each time, and continue to add steel fibers until all steel fibers are added after no steel fibers are visible on the visible surface of the mixer; S5: After the last batch of steel fibers is added, continue stirring for about 1 minute, take out the concrete, and pour it into the mold; S6: After one day of curing at room temperature, demoulding is performed. Check the apparent color difference and the presence of pores.

[0027] The prepared kaolin-dye-water reducer synergistically dispersed colored UHPC can be used in a range of applications including but not limited to exterior wall panels, imitation rock panels, and imitation ceramic panels, and can be pre-embedded with connectors inside, and can be well used in the construction industry, decoration industry, and daily necessities industry. Example 1

[0028] The raw materials include 950 parts of cement, 150 parts of kaolin, 50 parts of white silica fume, 1200 parts of quartz sand, 260 parts of steel fiber, 46 parts of water reducer, 207 parts of water, and 45 parts of dye.

[0029] A method for preparing colored UHPC with synergistic dispersion of metakaolin, dye and water reducing agent comprises the following steps: S1: Depending on the size of the prepared component, all the weight of the dye, 20% to 50% weight of the metakaolin, 50% to 100% weight of the water, and 100% weight of the water reducing agent are placed in a magnetic stirrer and stirred for about 10 minutes to form a preliminary stirring to form a mixed solution; S2: The mixed solution obtained in step S1 is placed in a magnetic stirrer and stirred for 10 minutes. After being stirred in the magnetic stirrer, all the mixed solution is taken out and placed in an ultrasonic disperser, and stirred at a power of 800 W for 10-20 minutes; S3: adding the mixed solution treated in step S2 into a concrete mixer, and adding the remaining cement, water, metakaolin, white silica fume, and quartz sand into the concrete mixer and stirring for 2-3 minutes until a plastic cement-based slurry is formed; S4: gradually add steel fibers into the concrete mixer, adding about 10% of the total amount of steel fibers each time, and continue to add steel fibers until all steel fibers are added after no steel fibers are visible on the visible surface of the mixer; S5: After adding the last batch of steel fibers, continue stirring for about 1 minute, take out the concrete and pour it into the mold.

[0030] S6: After one day of curing at room temperature, demould and check the apparent color difference and the presence of pores. Example 2

[0031] In the present embodiment, the raw materials include 976 parts of cement, 135 parts of metakaolin, 40 parts of white silica fume, 1316 parts of quartz sand, 230 parts of steel fiber, 35 parts of water reducer, 184 parts of water, and 45 parts of dye. Other steps are the same as in Example 1. Example 3

[0032] In the present embodiment, the raw materials include 1092 parts of cement, 205 parts of metakaolin, 68 parts of white silica fume, 1228 parts of quartz sand, 234 parts of steel fiber, 27 parts of water reducer, 218 parts of water, and 55 parts of dye. Other steps are the same as in Example 1. Example 4

[0033] In the present embodiment, the raw materials include 1092 parts of cement, 137 parts of metakaolin, 137 parts of white silica fume, 1228 parts of quartz sand, 234 parts of steel fiber, 27 parts of water reducer, 218 parts of water, and 55 parts of dye. Other steps are as in Example 1. Comparative Example 1

[0034] The raw materials include 950 parts of cement, 150 parts of metakaolin, 50 parts of white silica fume, 1200 parts of quartz sand, 260 parts of steel fiber, 46 parts of water reducer, 207 parts of water, and 45 parts of dye. The implementation steps include: mixing and stirring of dry mixed materials, in which the dye is added into the mixer together with cement, metakaolin, silica fume and quartz sand for stirring; stirring of plastic slurry, after the dry materials are evenly mixed, water and water reducer are added until plastic slurry is formed; steel fiber incorporation and molding casting, slowly adding steel fiber into the plastic slurry and continuously stirring until the steel fiber is evenly dispersed, taking out the mixture, and casting the mold for molding. Comparative Example 2

[0035] The raw materials include 976 parts of cement, 135 parts of kaolin, 40 parts of white silica fume, 1316 parts of quartz sand, 230 parts of steel fiber, 35 parts of water reducer, 184 parts of water, and 45 parts of dye. The implementation steps include: mixing and stirring of dry mixed materials, in which the dye is added into the mixer together with cement, kaolin, silica fume and quartz sand; stirring of plastic slurry, after the dry materials are evenly mixed, water and water reducer are added until plastic slurry is formed; steel fiber incorporation and molding casting, slowly adding steel fiber into the plastic slurry and continuously stirring until the steel fiber is evenly dispersed, taking out the mixture, and casting the mold for molding. Comparative Example 3

[0036] The raw materials include 1092 parts of cement, 205 parts of metakaolin, 68 parts of white silica fume, 1228 parts of quartz sand, 234 parts of steel fiber, 27 parts of water reducer, 218 parts of water, and 55 parts of dye. The implementation steps include: mixing and stirring of dry mixed materials, in which the dye is added into the mixer together with cement, metakaolin, silica fume and quartz sand for stirring; stirring of plastic slurry, after the dry materials are evenly mixed, water and water reducer are added until plastic slurry is formed; steel fiber incorporation and molding casting, slowly adding steel fiber into the plastic slurry and continuously stirring until the steel fiber is evenly dispersed, taking out the mixture, and casting the mold for molding. Comparative Example 4

[0037] The raw materials include 1092 parts of cement, 137 parts of metakaolin, 137 parts of white silica fume, 1228 parts of quartz sand, 234 parts of steel fiber, 27 parts of water reducer, 218 parts of water, and 55 parts of dye. The implementation steps include: mixing and stirring of dry mixed materials, in which the dye is added into the mixer together with cement, metakaolin, silica fume and quartz sand for stirring; stirring of plastic slurry, after the dry materials are evenly mixed, water and water reducer are added until plastic slurry is formed; steel fiber incorporation and molding casting, slowly adding steel fiber into the plastic slurry and continuously stirring until the steel fiber is evenly dispersed, taking out the mixture, and casting the mold for molding.

[0038] Performance tests were performed on each embodiment and comparative example, wherein the working performance of the mixture was measured with reference to the "Standard for Test Methods for Performance of Ordinary Concrete Mixtures" (GB / T 50080-2016), and the compressive strength was measured after 28 days of standard curing, and the test method was referenced to the "Standard for Test Methods for Physical and Mechanical Properties of Concrete" (GB / T50081-2019). The autogenous shrinkage test method of concrete was referenced to the "Standard for Test Methods for Long-term Performance and Durability of Ordinary Concrete" (GB / T 50082-2009). The results are shown in Table 1.

[0039] Table 1

[0040] As shown in Table 1, the compressive strength and working performance of Examples 1-4 are better than those of Comparative Examples 1-4. Analysis shows that the dyes that have not been dispersed in a coordinated manner cannot be uniformly stirred in the dry material mixing, and some of the cementitious material particles are wrapped and agglomerated by the dyes, which delays the hydration process and thus affects the macroscopic mechanical properties of the material. At the same time, the dyes have a large water absorption, which results in some mixing water being unable to participate in hydration, affecting the fluidity of the mixture. In addition, the colors of the two after molding are quite different, such as Figure 1 As shown in the figure, the surface color of the UHPC specimen treated with synergistic dispersion is uniform and bright, and there are no obvious defects or holes on the surface. Figure 2 The surface color of the UHPC specimens that have not been treated with synergistic dispersion is obviously dark and slightly dull, with uneven color distribution. In addition, due to poor fluidity, there are some pores and defects on the surface, which affects the appearance.

[0041] In summary: This application overcomes the problems of uneven dye dispersion, dye agglomeration, easy fading, and sticking to hands in the prior art. The present invention uses a new collaborative dispersion method, the purpose of which is to optimize the color UHPC technology and solve technical problems such as uneven dye dispersion, dye agglomeration, easy fading, sticking to hands, and reduced fluidity. Through the collaborative dispersion of metakaolin-dye-water reducer, the dye can be evenly dispersed in the metakaolin that is smaller than cement particles in the system, so that the dye is evenly dispersed, the dye does not agglomerate, has high durability, does not fade, and does not stick to hands. The prepared colored UHPC with collaborative dispersion of metakaolin-dye-water reducer can be used in a range of applications including but not limited to exterior wall panels, imitation rock panels, and imitation ceramic panels, and the internal connectors can be pre-embedded, which can be well used in the construction industry, decoration industry, and daily necessities industry.

[0042] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A color UHPC with synergistic dispersion of metakaolin, dye and water reducing agent, characterized in that: The colored UHPC comprises cement, metakaolin, white silica fume, quartz sand, water, steel fiber, water reducing agent and dye.

2. The color UHPC of metakaolin-dye-water reducing agent synergistic dispersion as claimed in claim 1, characterized in that: Calculated by mass, cement is 950-1100 parts, metakaolin is 150-200 parts, white silica fume is 0-150 parts, quartz sand is 1000-1400 parts, steel fiber is 100-400 parts, water reducer is 40-80 parts, water is 189-270 parts, and dye is 30-70 parts.

3. The color UHPC of metakaolin-dye-water reducing agent synergistic dispersion as claimed in claim 2, characterized in that: The cement is PO 52.5 white cement with a whiteness of ≥85; the specific surface area of ​​the metakaolin is ≥15 m 2 / g, whiteness ≥90; the specific surface area of ​​the white silica fume ≥12 m 2 / g, whiteness ≥90.

4. The color UHPC of metakaolin-dye-water reducing agent synergistic dispersion as claimed in claim 3, characterized in that: The quartz sand particles range from 0.106 to 0.212 mm; the water reducer is a polycarboxylic acid water reducer; the steel fiber has a length of ≥12 mm and a diameter of ≤0.2 mm.

5. The color UHPC of metakaolin-dye-water reducing agent synergistic dispersion as claimed in claim 4, characterized in that: The dye is an iron oxide based dye for concrete.

6. The method for preparing a colored UHPC with synergistic dispersion of metakaolin, dye and water reducing agent according to any one of claims 1 to 5, characterized in that: The following steps are involved: S1: Depending on the size of the prepared component, all the weight of dye, 20% to 50% weight of kaolin, 50%-100% weight of water, and 100% weight of water reducer are placed in a magnetic stirrer and stirred for 10 minutes to form a preliminary stirring to form a mixed solution; wherein the weight ratio of dye: kaolin: water: water reducer is (2-3): (3-5): (5-10): (2-3); S2: Put the mixed solution obtained in step S1 into a magnetic stirrer and stir for 10 minutes. After stirring in the magnetic stirrer, take out all the mixed solution, put it into an ultrasonic disperser, and stir it at a power of 800 W for 10-20 minutes. S3: adding the mixed solution treated in step S2 into a concrete mixer, and adding the remaining cement, water, metakaolin, white silica fume, and quartz sand into the concrete mixer for stirring for 2-3 minutes until a plastic cement-based slurry is formed; S4: gradually add steel fiber into the concrete mixer, adding 10% of the total amount of steel fiber each time, and continue to add steel fiber until all steel fiber is added after no steel fiber is visible on the visible surface of the mixer; S5: After the last batch of steel fibers is added, continue stirring for 1 minute, take out the concrete, and pour it into the mold; S6: After one day of curing at room temperature, demould and check the apparent color difference and the presence of pores.

7. A decorative board, characterized in that: The colored UHPC is made of the synergistically dispersed metakaolin-dye-water reducing agent described in any one of claims 1 to 5.

Citation Information

Patent Citations

  • Pigment dispersions and black water-reducing agent for cement

    CN102464900A

  • Color concrete and preparation method thereof

    CN102584144A

  • Colored ultra-high performance concrete and preparation method thereof

    CN111484292A

  • Colored concrete and preparation method thereof

    CN113461386A

  • Pigment agglomerates, their manufacture, and use

    CN1732236A

Cited By

  • Novel UHPC material for bridge expansion joints and preparation method thereof

    CN120962857A